218k views
1 vote
How do you simplify this?

How do you simplify this?-example-1

1 Answer

1 vote

Answer:

tan x

Explanation:

(tan-x)[sec(pi/2)-x] (sin-x)

We know that tan (-x) = - tan (x) and sin (-x) = - sin (x)

-(tanx)[sec(pi/2)-x] -(sinx)

(tanx)[sec(pi/2)-x] (sinx)

Using the identity sec = 1/ cos

sec ( pi/2 -x) =1/cos ( pi /2 -x)

We know that cos (s-t)=cos (s) cos(t) + sin (s) sin (t)

1/ ( cos pi/2 cos x + sin pi/2 sin x) = 1/(0 cos x - 1 sinx) = 1 / sinx

Replacing into the equation

(tanx)[1/ sinx] (sinx)

tan x

User Kimmarie
by
5.1k points